Price analysis and forecasting patterns of maize grown in the states of Tamil Nadu and Karnataka - Kasmeer , R J; Mahendran, K; Selvanayaki, S; Parimalarangan, R; Anandhi, V (Plant Science Today, 2025)
Maize (Zea mays L.) is the most important cereal crop in India. It serves as a vital component in the food, feed and industrial sectors and contributing significantly to the agricultural economy. This study analyses the price dynamics and forecasting patterns of maize in India, with a specific focus on the regional markets of Salem in Tamil Nadu and Haveri in Karnataka, over a 10-year period from 2015 to 2024. A comprehensive time series analytical framework was employed, incorporating tools such as the Compound Annual Growth Rate (CAGR), seasonal indices, standard deviation and coefficient of variation, along with the Autoregressive Integrated Moving Average (ARIMA) model, to investigate trends, seasonal behaviour, price volatility and price forecasting. This study highlights long-term trends in the area, production and yield of maize at both national and state levels. The studies revealed that Tamil Nadu demonstrated comparatively stronger growth performance than Karnataka, with higher averages across all parameters. This advantage could be attributed primarily to improved irrigation infrastructure, adoption of hybrid varieties and targeted policy support. Seasonal index analysis uncovered distinct price movement patterns, with Salem showing seasonal peaks in August and Haveri in September, coinciding with lean supply months. Price volatility analysis showed moderate fluctuations, with Salem exhibiting slightly greater variability. The ARIMA model predicted a gradual rise in maize prices from July to December 2025 in both markets. This research provides meaningful insights for farmers, traders, policymakers and agri-business firms to develop better crop planning, price risk management and marketing strategies.